1996
DOI: 10.1159/000109668
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Predictors of Dementia in Elderly Community Residents

Abstract: Detection of subjects with a high risk of developing dementia is a major goal of epidemiological research. Among the potential predictors, minor cognitive impairments detected by psychometric methods could be important precursors. A total of 2,726 elderly nondemented subjects, aged 65 and over, randomly selected from the general population of Gironde (southwestern France) were followed up for 3 years. During this time, 84 developed an incident dementia, diagnosed as Alzheimer''s disease (AD) in 59. The relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…One was a subjective memory complaint, which was reported by 17% of future AD patients and none of those who remained healthy. Subjective memory impairment has been found to be a harbinger of further decline in subjects with no cognitive impairment at study entry [31] and has been reported to be an early and strong predictor of AD [32,53]. Similarly, 17% of AD-P and none of the NC participants reported current cardiac problems.…”
Section: Discussionmentioning
confidence: 99%
“…One was a subjective memory complaint, which was reported by 17% of future AD patients and none of those who remained healthy. Subjective memory impairment has been found to be a harbinger of further decline in subjects with no cognitive impairment at study entry [31] and has been reported to be an early and strong predictor of AD [32,53]. Similarly, 17% of AD-P and none of the NC participants reported current cardiac problems.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that such subjects have a lower cognitive level than those who complete the test. 38 In the context of the present study, it appeared interesting to include the total population of subjects. In order to determine the two modalities, the threshold which displayed the best separation between subjects who had ceased driving and those who continued driving, was computed using the maximum likelihood for the univariate logistic regression model.…”
Section: Discussionmentioning
confidence: 99%
“…The Paquid Study is designed to determine the prevalence and incidence of dementias and AD in people over 3 65 years in the South-West of France. This study has carefully assessed the predictive value of psychometric performance [3] and of memory complaints either isolated or associated with objective abnormalities observed by neuropsychological examinations.…”
Section: Oooooooooooooooooooooomentioning
confidence: 99%
“…This study has carefully assessed the predictive value of psychometric performance [3] and of memory complaints either isolated or associated with objective abnormalities observed by neuropsychological examinations. The incidence of dementias varies from 0.4 per 100 person-years in normal subjects without memory complaint to 3.6 per 100 personyears in patients with memory complaint and objective impairment.…”
Section: Oooooooooooooooooooooomentioning
confidence: 99%